High total organic carbon in surface waters of the northern Arabian Gulf: Implications for the oxygen minimum zone of the Arabian Sea. Issue 1 (April 2018) - Al-Said, Turki; Naqvi, S.W.A.; Al-Yamani, Faiza; Goncharov, Alexandr; Fernandes, Loreta
Abstract: Measurements of total organic carbon (TOC) for two years in Kuwaiti waters showed high TOC levels (101.0–318.4, mean 161.2 μM) with maximal concentrations occurring within the polluted Kuwait Bay and decreasing offshore, indicating substantial anthropogenic component. Analysis of winter-time data revealed a large increase in density over the past four decades due to decrease in Shatt Al-Arab runoff, implying that the dissolved/suspended organic matter in surface waters of the northern Gulf could be quickly injected into the Gulf Deep Water (GDW). Our measurements together with an analysis of previously collected/published data suggest that the recent summer-time declining trend in oxygen in the GDW might be related to eutrophication. Higher preformed TOC and lower preformed dissolved oxygen contents of the high-salinity water mass that flows out of the Gulf and ventilates the mesopelagic oxygen minimum zone (OMZ) of the Northwestern Indian Ocean may cause expansion/intensification of the regional OMZ. Highlights: This is the first study of total organic carbon (TOC) in the northern Arabian Gulf. High TOC concentrations in Kuwait waters attributed to human activities. Large salinity increase producing waters with highest density off Kuwait in winter. Seasonal hypoxia in the Gulf is of recent origin, attributed to eutrophication. Increase in TOC in Gulf Outflow likely to promote deoxygenation in NW Indian Ocean.